Assessing the Productive Power of Companies with Profitability Ratios - Suwandi; Melinda; Dahlia Br. Pinem; Marlina; A. Besse Dahliana (INFLUENCE: INTERNATIONAL JOURNAL OF SCIENCE REVIEW, 2023)
Productivity assessment is classified as an important aspect in measuring the operational success of a company whose implementation has not been optimally implemented by some companies in Indonesia, even in the world. The purpose of this qualitative-descriptive study is to analyze the level of profitability in assessing company productivity at CV Sinar Surya Parepare Branch-South Sulawesi. This study involves the company's financial statements as research objects obtained through documentation techniques. The observation period in this study takes five periods, namely 2017 to 2021. These findings inform that the analysis of ROA and ROE ratios does not provide guarantees for increasing company productivity. However, through this analysis, the level of efficiency in the use of company resources can be directly identified. On the other hand, through this efficiency encourages increased company productivity. Following up on the findings of this study, an assessment of company productivity must be carried out on an ongoing basis through the analysis referred to in this study combined with other assessment models.